Transporter‐mediated replacement of extracellular glutamate for GABA in the developing murine neocortex. Issue 11 (9th October 2013) - Unichenko, Petr; Dvorzhak, Anton; Kirischuk, Sergei
Abstract During early development, cortical neurons migrate from their places of origin to their final destinations where they differentiate and establish synaptic connections. During corticogenesis, radially migrating cells move from deeper zone to the marginal zone, but they do not invade the latter. This "stop" function of the marginal zone is mediated by a number of factors, including glutamate and γ‐aminobutyric acid (GABA), two main neurotransmitters in the central nervous system. In the marginal zone, GABA has been shown to be released via GABA transporters (GAT)‐2/3, whereas glutamate transporters (EAATs) operate in the uptake mode. In this study, GABAergic postsynaptic currents (GPSCs) were recorded from Cajal‐Retzius cells in the marginal zone of murine neonatal neocortex using a whole‐cell patch‐clamp technique. Minimal electrical stimulation was applied to elicit evoked GPSCs using a paired‐pulse protocol. EAAT blockade with dl‐threo‐b‐benzyloxyaspartic acid (dl‐TBOA), a specific non‐transportable EAAT antagonist, abolishes constitutive GAT‐2/3‐mediated GABA release. In contrast to dl‐TBOA, d‐aspartate, an EAAT substrate, fails to block GAT‐2/3‐mediated GABA release. SNAP‐5114, a specific GAT‐2/3 antagonist, induced an elevation of intracellular sodium concentration ([Na+]i) under resting conditions and in the presence of d‐aspartate, indicating that GAT‐2/3 operates in reverse mode. In the presence of dl‐TBOA, however, SNAP‐5114 elicited a [Na+]i decrease, demonstrating that GAT‐2/3 operates in uptake mode. We conclude that EAATs via intracellular Na+ signaling and/or cell depolarization can govern the strength/direction of GAT‐mediated GABA transport.